SOCS6 Functions as a Tumor Suppressor by Inducing Apoptosis and Inhibiting Angiogenesis in Human Prostate Cancer - Yuan, Dongbo; Wang, Wei; Su, Jiaming; Zhang, Yongqiang; Luan, Boshi; Rao, Haofu; Cheng, Tianfei; Zhang, Wei; Xiao, Shiwei; Zhang, Mingsheng; Jiang, Fu-Neng; Sun, Zhaolin; et al. (Current Cancer Drug Targets, 2018)
Background: Our previous studies revealed that the downregulation of Suppressor of cytokine signaling 6 (SOCS6) was correlated with malignant progression of human prostate cancer (PCa). Aims: In the current study, we aimed to investigate the tumor suppressive roles of SOCS6 and the underlying mechanisms in PCa. Methods: SOCS6 expression in PCa and non-cancerous prostate tissues was compared by immunohistochemistry. Statistical associations of SOCS6 expression with various clinicopathological features and patients prognosis were evaluated. In addition, we investigated SOCS6's functions by overexpressing it in vitro (cell apoptosis, migration and invasion assays) and in vivo (tumor formation, angiogenesis and apoptosis). Moreover, SOCS6-regulated genes were identified by nextgeneration RNA-sequencing analysis, followed by pathway enrichment analysis and in vitro experimental validation. Results: SOCS6 downregulation was significantly associated with advanced clinical stage (P=0.029) and positive lymph node metastasis (P=0.013) in PCa patients. We also identified SOCS6 as an independent prognostic factor for disease-free survival in PCa patients (P=0.045). Moreover, overexpression of SOCS6 inhibited PCa cell invasion, migration, tumor xenografts growth and angiogenesis, but induced PCa cell apoptosis (P values <0.05). Mechanically, we revealed that SOCS6 expression may induce cell apoptosis coincident with down-regulation of Bcl2 and Hspa1a, and may suppress tumor angiogenesis with downregulation of F7, Fak3 and Frzb. Conclusion: These findings suggest that the reduced expression of SOCS6 may be predictive of unfavorable prognosis in PCa. Thus, SOCS6 may serve as a tumor suppressor and a novel therapeutic target for this cancer.
Keywords: tumor suppressor